Digital Transformational Leadership: A Bibliometric Study of Digital Transformation Trends, Themes, and Challenges in Organizations - Kismiadi, Kismiadi; Firdaus, Rahmad; Suhardi, Suhardi (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
Digital transformation has become the centre of attention in modern organizational strategies, especially in the context of digital transformational leadership. This research aims to map the intellectual structure and global research trends related to these themes through a bibliometric approach. Data were obtained from the ScienceDirect database using the keyword